Frequency of Gastrointestinal Signs and Symptoms in Patients with Dengue Fever in Tertiary Care Hospital - Taqdees Abrar, Tayyeba Selamat, Anwar Hussain Abbasi, Hafsa Javaid Cheema, Shazma Ahmed, Maryam Zaka, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective behind this study was to determine the frequency of gastrointestinal signs and symptoms in patients with dengue fever in tertiary care hospital Methods: A cross sectional observational study was conducted on all adult patients diagnosed with dengue disease after taken informed consent from the patients and approval from the ethical committee of the hospital. All these patients were evaluated for the presence or absence of gastrointestinal (GI) manifestations. Those who had GI symptoms were further evaluated for the frequency of different types of GI symptoms. All baseline and clinical data were taken using a structured questionnaire and then entered & analysed using SPSS v. 26. Results: A total of 174 patients who were dengue virus positive were included for final analysis. Overall mean age and SD was 29.22±8.14 years and majority belongs to young age group, ≥16 – 40 years (60.11%, n = 104). Most of our study participants were males (75.86%, n = 132). Hypertension was the most common comorbid condition observed in our study participants (12.06%, n = 21). The overall prevalence of GI manifestations in our study who were dengue positive was 62.64% (n = 109). The most common GI symptom was presence of nausea/vomiting (70.64%, n = 77). Conclusion: The prevalence of GI manifestations in patients with dengue is quite high. Nausea/vomiting was the most common GI manifestation while patients with hepatomegaly and GI bleeding were also prevalent. Keywords: Dengue fever, gastrointestinal symptoms, clinical manifestation, Pakistan